The Relationship Between Parenting Patterns With The Discipline Of Youth In Nanggalo Koto XI Tarusan District - Sepy Fadhillah Fadhillah; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research is based on the low self-discipline of adolescents in Kenagarian Nanggalo, Koto XI Tarusan District. This is thought to be influenced by the parenting style of parents in paying attention to discipline in their education. The objectives of this study are (1) to see the description of parenting patterns according to adolescents in Nanggalo, Koto XI Tarusan District. (2) To see the description of adolescent discipline in Nanggalo, Koto XI Tarusan District. (3) To see the relationship between parenting and discipline in adolescents. in Kenagarian Nanggalo, Koto XI Tarusan District. The type of this research is descriptive quantitative research, correlation analysis method. The population is 26 people, the sampling technique is random sampling and taken by 60% or as many as 16 people. This study showed several results, namely: (1) Adolescent parenting in Nanggalo District Koto XI Tarusan was categorized as poor. This is evidenced by the parents not educating their children well, the parents not guiding and disciplining their children properly; (2) Adolescent self-discipline in Nanggalo, Koto XI Tarusan District is categorized as low. It can be seen that children have not been able to obey the rules seriously and are less obedient in disciplining themselves; (3) Has a significant relationship between parenting and adolescent self-discipline in Nanggalo, Koto XI Tarusan District.